My first look at home - Shone, Karl; Random House (Firm) (New York : Random House, 1990)
Text and photos depict objects from different rooms in the home, such as kitchen, bathroom, living room, playroom, and garage.
"First published in Great Britain by Dorling Kindersley Publishers Limited in 1990"--P. 1.
School Library Journal
1.5
K-3
Keywords: Dwellings -- Juvenile literature; Dwellings; Houses